Using effective language learning strategies in teaching English - Kaipbergenova Dilbar Orakbayevna (Zien Journals, 2022)
Research about learning strategies has focused on language learning and teaching in order to provide insights for developing effective vocabulary teaching and learning. Although vocabulary has been attributed less importance than the four skills in language teaching, interest in its role in language learning has grown rapidly in recent years because learning a foreign language is basically a matter of learning the vocabulary of that language. In a foreign language learning context, it cannot be denied that vocabulary is an element of great importance and thus emphasized to a great extent.
Keywords: Method; vocabulary; Semantic Mapping technique; materials